Space phobia: syndrome or agoraphobic variant?. Issue 6031 (7th August 1976) - Marks, I; Bebbington, P
Abstract : Four elderly women had intense fears of falling when there was no visible support at hand or on seeing space cues while driving. Two patients had cervical spondylosis. The mean age at onset of the fear was 54--thirty years later than that for agoraphobia. Fear of public places and of heights was not prominent, nor was depersonalisation or depression. These "space phobias" might be a hitherto unrecognised syndrome or an unusual variant of agoraphobia. The visuospatial reflexes involved might illuminate the pathogenesis of certain fears.